2015
DOI: 10.1016/j.ceb.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between stem cell and cell cycle machineries

Abstract: Pluripotent stem cells, defined by an unlimited self-renewal capacity and an undifferentiated state, are best typified by embryonic stem cells. These cells have a unique cell cycle compared to somatic cells as defined by a rapid progression through the cell cycle and a minimal time spent in G1. Recent reports indicate that pluripotency and cell cycle regulation are mechanistically linked. In this review, we discuss the reciprocal co-regulation of these processes, how this co-regulation may prevent differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 71 publications
1
37
1
Order By: Relevance
“…It has long been known that the durations of these phases can vary considerably across cell types (Dawson et al, 1965). For example, stem cells and immune cells have relatively brief G1 durations compared to somatic cells (Becker et al, 2006;Kareta et al, 2015;Kinjyo et al, 2015). Phase durations can also change under certain environmental stresses such as starvation, which lengthens G1 (Cooper, 2003), or DNA damage, which mainly prolongs G1 and G2 (Arora et al, 2017;Chao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that the durations of these phases can vary considerably across cell types (Dawson et al, 1965). For example, stem cells and immune cells have relatively brief G1 durations compared to somatic cells (Becker et al, 2006;Kareta et al, 2015;Kinjyo et al, 2015). Phase durations can also change under certain environmental stresses such as starvation, which lengthens G1 (Cooper, 2003), or DNA damage, which mainly prolongs G1 and G2 (Arora et al, 2017;Chao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cell fate switches correlation with cell cycle transition in dividing cells, whereas terminal differentiation is frequently associated with cell cycle exit. It is reported that the rapid cell division supports the selfrenewal of hESCs because of the shortened G1 cell cycle [14]. Cell cycle length and rate are determining factors for both self-renewal and differentiation of stem cells, so cell cycle analyses have value to determine the differentiation progress of hPSCs [15].…”
Section: The Cell Cycle Changes Of Hpscs During Osteogenic Differentimentioning
confidence: 99%
“…In multicellular animals, only a handful of genes have been identified to play a central role in both cell cycle control and establishment of developmental processes. Recent studies provide evidence on the links between cell cycle and development, and emphasize the role of Geminin on fate commitment programs in stem and progenitor cells .…”
Section: Geminin a Regulator Of Lineage Specificationmentioning
confidence: 99%